Pengaruh Persepsi Kemudahan, Persepsi Manfaat, Fitur Layanan, Promosi dan Keamanan Terhadap Keputusan Penggunaan E-Wallet Dana pada Generasi Z di Depok - Yuli Febriyani; Wardoyo Wardoyo (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
With the development of financial technology and the increasing use of digital wallets, understanding the factors that influence users' decisions in choosing e-wallet services is becoming increasingly important. The purpose of this study is to analyze the influence of Perceived Ease, Perceived Benefits, Service Features, Promotions, and Security on the Decision to Use the DANA E-Wallet among Generation Z in Depok. The data used in this study is primary data obtained from an online questionnaire distributed using Google Forms. There were 210 respondents using non-probability sampling with the snowball sampling method. The variables in this study are perceived ease of use, perceived usefulness, service features, promotion, security, and usage decision as the dependent variable. The test tool used PLS-SEM with the help of SmartPLS 4.0 to process the data. The results showed that the variables of perceived ease, perceived benefits, service features, and security had a partial effect on the decision to use the DANA e-wallet among Generation Z in Depok, while promotion had no partial effect on the decision to use the DANA e-wallet among Generation Z in Depok. This study also shows that perceived ease of use, perceived usefulness, service features, promotion, and security simultaneously influence the decision to use the DANA e-wallet among Generation Z in Depok, and that the security variable has the greatest influence on the decision to use the DANA e-wallet among Generation Z in Depok.